2019
DOI: 10.4103/jcas.jcas_136_18
|View full text |Cite
|
Sign up to set email alerts
|

Noncultured extracted hair follicle outer root sheath cell suspension versus noncultured epidermal cell suspension in the treatment of stable vitiligo

Abstract: Background: Various treatment modalities exist for vitiligo, yet none of them are curative. Vitiligo is still considered a challenging disease to manage. Surgical treatment offers an excellent option for patients with stable vitiligo, especially those who fail to respond to medical treatment. Cell suspension techniques carry the advantage of covering large surface areas. Objective: To compare noncultured extracted hair follicle outer root sheath cell suspension (NCORSHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…We analyzed a total of 117 unique studies with 8776 unique patients (eTable 1 in the Supplement), including 19 studies with 1631 patients in the punch grafting group, 10 studies with 718 patients in the thin skin grafting group, 29 studies with 2652 patients in the suction blister grafting group, 45 studies with 2209 patients in the noncultured epidermal cell suspension (NCES) group, 9 studies with 185 patients in the noncultured follicular cell suspension (NCFS) group, and 17 studies with 1381 patients in the cultured epidermal cell suspension (CES) group; 11 studies included more than 1 procedure type. The median follow-up duration was 7 (range, 2-108) months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed a total of 117 unique studies with 8776 unique patients (eTable 1 in the Supplement), including 19 studies with 1631 patients in the punch grafting group, 10 studies with 718 patients in the thin skin grafting group, 29 studies with 2652 patients in the suction blister grafting group, 45 studies with 2209 patients in the noncultured epidermal cell suspension (NCES) group, 9 studies with 185 patients in the noncultured follicular cell suspension (NCFS) group, and 17 studies with 1381 patients in the cultured epidermal cell suspension (CES) group; 11 studies included more than 1 procedure type. The median follow-up duration was 7 (range, 2-108) months.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the rate of repigmentation achieved by patients after 1 session of any surgical intervention included greater than 90% in 52.69% (95% CI, 46.87%-58.50%) in 106 studies with 6586 patients ( I 2 = 97.2%) (eFigure 2 in the Supplement); greater than 75% in 64.72% (95% CI, 59.52%-69.92%) in 100 studies with 3400 patients ( I 2 = 95.7%); and greater than 50% in 81.01% (95% CI, 78.18%-83.84%) in 92 studies with 5462 patients ( I 2 = 90.7%). According to the surgical intervention type, greater than 90% repigmentation was achieved in 72.08% (95% CI, 54.26%-89.89%) of patients undergoing thin skin grafting (670 patients in 8 studies), 61.68% (95% CI, 47.44%-75.92%) of patients undergoing suction blister grafting (2349 patients in 21 studies), 56.82% (95% CI, 48.93%-64.71%) of patients undergoing CES (1138 patients in 14 studies), 47.51% (95% CI, 37.00%-58.03%) of patients undergoing NCES (907 patients in 29 studies), 45.76% (95% CI, 30.67%-60.85%) of patients undergoing punch grafting (1354 patients in 11 studies), and 36.24% (95% CI, 18.92%-53.57%) of patients undergoing NCFS (160 patients in 8 studies) after 1 session of each surgery (eFigure 2 in the Supplement and Table 1). In our meta-regression analysis, for greater than 90% repigmentation, the estimate of the slopes for mean age of patients was −1.1418 ( P = .02); for the proportion of segmental vitiligo, 0.3047 ( P = .01); and for the proportion of treated lesions on the acral and joint areas, −0.4050 ( P = .002) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…[ 18 ] In Group A, 4 (20%) lesions presented with secondary infection on the 2nd week of follow-up, and 1 (5%), 2 (10%), and 4 (20%) lesions showed hyperpigmentation at 4th, 8th, and 12th week, respectively. A recent study conducted by Hamza et al [ 19 ] showed no complication at the recipient site. This difference could be due to exposure of sunlight during the postoperative period in our patients as compared to the controlled exposure of Narrow Band UVB used by Hamza et al [ 19 ] At the donor site, 2 (10%) lesions presented with infection after 2 weeks and 1 (5%) lesion developed hyperpigmentation at 4th week.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted by Hamza et al [ 19 ] showed no complication at the recipient site. This difference could be due to exposure of sunlight during the postoperative period in our patients as compared to the controlled exposure of Narrow Band UVB used by Hamza et al [ 19 ] At the donor site, 2 (10%) lesions presented with infection after 2 weeks and 1 (5%) lesion developed hyperpigmentation at 4th week. A study conducted by Leelavathy et al [ 20 ] showed hyperpigmentation in 43% and scarring in 13% of their patients at the donor site.…”
Section: Discussionmentioning
confidence: 99%
“…23 Evaluation was made by a blinded investigator. At 3 months, response was assessed using point counting, 14 VESTA score, 15 PGA, 23 patient satisfaction 24 and colour match. 25…”
Section: Postprocedural Assessmentmentioning
confidence: 99%